MULTIDIMENSIONALITY OF SCHOOL DROPOUT IN TECHNICAL AND SECONDARY EDUCATION (Fiep Bulletin - online, 2025)
Introduction: School dropout in Brazil is a critical challenge at the secondary and technical levels, affecting student retention and prospects, with multifactorial causes such as socioeconomic, pedagogical, and institutional barriers. Objective: To investigate the factors associated with school dropout at Brazil's secondary and technical education levels, focusing on student retention dynamics. Methods: A narrative literature review was conducted, searching SciELO, Scopus, and Web of Science databases for studies published between 2010 and 2024. Articles in Portuguese, English, or Spanish addressing factors related to school dropout at the secondary and technical levels were analyzed. Results: School dropout at these levels is driven by adverse socioeconomic conditions, lack of motivation, inadequate pedagogical practices, and insufficient institutional support. Vulnerable groups such as Black adolescents, LGBTQIAP+ youth, those in extreme poverty, and students with special educational needs are at greater risk of leaving school. Conclusion: School dropout reflects a multifactorial issue that demands integrated public policies and consistent institutional actions to address its causes and promote retention and academic success.
Keywords: School dropout; technical education; secondary education